STRESS EVOLUTION INDUCED BY CHARGING SHUT-DOWN IN LITHIUM-ION BATTERIES - ZHAO YanFei; LV Bo (Jixie qiangdu)
A short interruption occuring during the charging process influences the stress evolution. Two cases were considered here. In one case the galvanostatic charging process was interrupted while in the other case the potentiostatic charging process was interrupted. By solving the diffusion equation with an initial condition of general form,the analytical solutions of the concentration variation as well as the stress evolution of these two cases were obtained. Charging interruption leads to a short moment of stress relaxtion,but the stress recovers to increase once the charging is turned on again. Each time of interruption results in a rise-and-fall of the diffusion-induced stress. The longer the interruption lasts,the more severe the stress fluctuation is,which is dentrimental to the battery life. The up-and-down phenomenon in the stress is more obvious for interrupting the galvanostatic stage than for interrupting the potentiostatic stage. The most severe stress fluctuation occurs when the interruption happens near the switching moment between the galvanostatic stage and the potentiostatic stage.